Cybercrime investigation case studies an excerpt from Placing the suspect behind the keyboard - Shavers, Brett (Syngress, 2013)
Case studies are an effective method of learning the methods and processes that were both successful and unsuccessful in real cases. This title teaches you how to place the suspect behind the keyboard using case studies.